Three-Dimensional Evolution of Mesoscale Anticyclones in the Lee of Crete - Ioannou, Artemis; Stegner, Alexandre; Dumas, Franck; Le Vu, Briac (Frontiers in Marine Science, 2020)
Motivated by the recurrent formation of mesoscale anticyclones in the southeast of Crete, we investigated with a high resolution model the response of the ocean to orographic wind jets driven by the Cretean mountain range. As shown in the dynamical process study of Ioannou et al. (2020) which uses a simplified shallow-water model, we confirm here, using the CROCO (Coastal and Regional Ocean COmmunity) model, that the main oceanic response to the Etesian wind forcing is the formation of mesoscale anticyclones. Moreover, we found that the intensity of the wind-induced Ekman pumping acting on the eddies, once they are formed, modulates their intensity. Among the various coastal anticyclones formed during summer and fall 2015, only one of them will correspond to a long lived structure (M_IE15) which is similar to the Ierapetra Eddy detected in 2015 (O_IE15) on the AVISO/DUACS products. Thanks to the DYNED-Atlas data base, we were able to perform a quantitative comparison of the vertical structure of such long-lived anticyclone between the numerical model and the in-situ measurements of the various Argo profilers trapped inside the eddy core. Even without assimilation or any nudging, the numerical model was able to reproduce correctly the formation period, the seasonal evolution and the vertical structure of the O_IE15. The main discrepancy between the model and the altimetry observations is the dynamical intensity of the anticyclone. The characteristic eddy velocity derived from the AVISO/DUACS product for the O_IE15 is much lower than in the numerical model. This is probably due to the spatio temporal interpolation of the AVISO/DUACS altimetry products. More surprisingly, several coastal anticyclones were also formed in the model in the lee of Crete area during summer 2015 when the Etesian winds reach strong values. However, these coastal anticyclones respond differently to the wind forcing since they remain close to the coast, in shallow-waters, unlike the O_IE15 which propagates offshore in deep water. The impact of the bottom friction or the coastal dissipation seems to limit the wind amplification of these coastal anticyclones.